Organizing digital competence development in preschools: Professionals’ insights from three Swedish municipalities - Marianne Gallardo (Journal of Childhood, Education & Society)
This article contributes to the understanding of how digital competence development (DCD) for preschool educators is organized across three Swedish municipalities, focusing on communal preschools and drawing on participants’ experiences. With a case study approach, the research addresses the growing need for DCD to integrate digital technology into pedagogy in preschool. Continuing professional development like this can be initiated and shaped through various methods, including formal education, courses, and programs. Another often more efficient approach is to support and enhance continuous, day-to-day learning in the workplace. However, in-depth research on such workplace learning and practice is lacking despite ongoing debates on digital tool use in early childhood education. Fifteen interviews with operational developers, development leaders, principals, and information and communication technology (ICT) educators serve as the basis for this study. Billet's theories on workplace learning frame the analysis, studying the organizing of DCD through the interdependence between possible learning opportunities (affordances) and the influences it has on individuals’ agency (engagement) within the cases. Findings highlight that ICT educators played a pivotal role in coaching and shaping professional development, suggesting that the learning opportunities available to staff were significantly influenced by the motivation and engagement of self-driven individuals, along with principal prioritization and municipal vision. This study also shows the availability of DCD through collegial cooperation, dedicated support groups and networks. The study underscores the importance of workplace learning for enhancing preschool educators' digital competence and proposes practical strategies to facilitate staff support.